Eliminating Viral Hepatitis from India and Southeast Asia by 2030: Challenges and Ways Forward - Senthilkumar Ramasamy; Bitty Raghavan; Sreeshma Pavithran; Swati Misra; Balaji Susindran; Chandrakant Lahariya (Preventive Medicine: Research & Reviews, 2024)
This review was conducted to understand the epidemiology of hepatitis in Southeast Asia, examine the current scenario, and suggest a way forward for elimination. A comprehensive desk review was followed by analysis and interpretation. Viral hepatitis fits the criteria for elimination. The availability of safe and effective vaccines against the hepatitis B virus and the effective treatments for the hepatitis C virus makes it possible to eliminate hepatitis. Stepping up interventions such as universal screening, identifying the hotspots, investing in the interventions for elimination, increasing hepatitis testing and linkage to care, attention on adult vaccination, increasing coverage with hepatitis B vaccination for kids, and making hepatitis C treatment available, accessible and affordable are the strategies which need to be expanded. Telemedicine, education and training and hybrid surveillance will help increase access to services for viral hepatitis prevention and treatment. Accelerated efforts to eliminate hepatitis from South East Asia are needed. Key stakeholders need to work together for this agreed goal. The countries need to learn from each other. The primary healthcare approach should be used to achieve the elimination goal.